Circulation, Translation, and Adaption of African Literary Works and Their Possible Positions in World Literature Anthologies - Martha, Ludmila (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2017)
World Literature is not all literature of the entire world but only literature which travels outside its country of origin.The circulation and reception of texts in a given cultural system can be complicated due to languages. However global awork may be in intention, it can be seen as just a would-be work of world literature unlessand until it actually finds readers abroad. By making anEnglish version of the novel accessible, many African writers couldmaintain their bargaining power, especially towards the circulation system of World Literature. African literature has also inspired several adaptations, since adaptation itself has a significant place in World Literature.Moreover, when African literary works are included in some anthologies, they could perform particular types of discourse. It could be inferred that the anthologies of African literary works by women writers are different from their male counterparts.Keywords: world literature, circulation, translation, adaptation, anthology